Clinical evaluation of periodontal pathogen levels by real-time polymerase chain reaction in peri-implantitis patients - Taichi Ito; Gentaro Mori; Yukari Oda; Tomoki Hirano; Hodaka Sasaki; Shinya Honma; Yoshitaka Furuya; Yasutomo Yajima (SpringerOpen, 2021)
Abstract Objective The mechanisms underlying the onset and progression of peri-implantitis are similar to those of periodontitis, and the causative bacteria are believed to similar. Previous studies support an association between peri-implantitis and periodontal pathogen. Thus, we investigated the bacterial flora of peri-implantitis patients in comparison to those of healthy implant and periodontitis patients. Materials and methods In total, 70 patients visiting Tokyo Dental College Chiba Hospital were divided into four groups: healthy, periodontitis, healthy implant, and peri-implantitis. For each group, the following five periodontal pathogens were detected using real-time polymerase chain reaction: Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, Tannerella forsythia, Treponema denticola, and Prevotella intermedia. Results The average copy number of total bacteria was significantly higher in the periodontitis group than in the other groups. P. gingivalis was detected in the periodontitis and peri-implantitis groups at levels as high as 18.92% and 12.29%, respectively, and P. intermedia was found in the peri-implantitis group at a rate of 2.06%. Nevertheless, periodontal pathogens were generally detected at lower levels in the peri-implantitis group than in the periodontitis group. Conclusion We found lower bacterial counts in the peri-implantitis group relative to the periodontitis group. Our results suggest that the peri-implant tissue is less resistant to bacteria, so even a small number of bacteria can be a risk factor for peri-implantitis and the causative agent of peri-implantitis can be bacteria other than periodontal pathogen.